Strategy for Determining Priority of Production Material Inventory with AHP Topsis and Monte Carlo Integration in Metal Stamping Industry - Novitasari, Ayu; Ishak, Dendi P. (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Optimal inventory management is key to the smooth production process in the manufacturing industry. Overstock and material shortages are challenges caused by fluctuations in demand and the types of materials with different characteristics. This research aims to develop a strategy for prioritizing material inventory that requires special attention compared to other inventories using AHP TOPSIS method, as well as to ensure the optimal inventory amount so that the material reorder process can be carried out accurately and efficiently using the monte carlo simulation method. The strategy used in determining the priority of reordering production materials is to establish a priority order of materials based on the level of importance. Material coil ranks first with the highest value of 0.530, followed by sheet metal, supported inv, chemical, shaft, and packaging material. Next, to determine the reorder quantity of coils using monte carlo simulation for three scenarios during the period from January to March 2025. The prediction results indicate that scenario 2 has an accuracy rate of 92%, so it is selected as the reference. The amount of coil material orders based on scenario 2 is 605,433 KGM for January, 676,097 KGM for February, and 549,784 KGM for March.